2017
DOI: 10.1111/asj.12771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xylanase supplementation on growth performance, nutrient digestibility, blood parameters, fecal microbiota, fecal score and fecal noxious gas emission of weaning pigs fed corn‐soybean meal‐based diet

Abstract: This study was conducted to evaluate the effects of xylanase supplementation on nutrient digestibility, growth performance, blood parameters, fecal microflora shedding, fecal score and fecal noxious gas emission of weaning pigs fed corn-soybean meal based diet. A total of 150 weaning pigs with an average initial body weight (BW) of 7.85 ± 0.93 kg were randomly allocated to three treatments based on BW and sex (10 replicate pens with five pigs, two gilts and three barrows) were used in this 42-day trial. Dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In this study, the addition of xylanase improved ADG and G:F in pigs fed a diet high in insoluble corn-based fiber, but these improvements were not detectable until between days 14 and 27 of supplementation and were even greater after day 27. This is in agreement with Lan et al (2017) who reported that xylanase improved the ADG of nursery pigs fed a corn–soybean meal-based diet from 15 to 28 d of supplementation and improved ADG and G:F from day 29 to 42, and with Myers and Patience (2014) who reported a tendency for xylanase to improve ADG in nursery pigs fed corn-based diets from day 23 to 28 of supplementation. Likewise, Fang et al (2007 ) reported improvements in final BW, ADG, and feed efficiency of growing pigs fed a corn–soybean–rapeseed meal-based diet for 49 d. However, there is a paucity of studies that report improved pig performance when xylanase is supplemented in diets containing corn DDGS, and this has been largely attributed to the level of NDF within the diet, and the composition of corn arabinoxylan ( Jacela et al, 2010 ; Kerr et al, 2013 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the addition of xylanase improved ADG and G:F in pigs fed a diet high in insoluble corn-based fiber, but these improvements were not detectable until between days 14 and 27 of supplementation and were even greater after day 27. This is in agreement with Lan et al (2017) who reported that xylanase improved the ADG of nursery pigs fed a corn–soybean meal-based diet from 15 to 28 d of supplementation and improved ADG and G:F from day 29 to 42, and with Myers and Patience (2014) who reported a tendency for xylanase to improve ADG in nursery pigs fed corn-based diets from day 23 to 28 of supplementation. Likewise, Fang et al (2007 ) reported improvements in final BW, ADG, and feed efficiency of growing pigs fed a corn–soybean–rapeseed meal-based diet for 49 d. However, there is a paucity of studies that report improved pig performance when xylanase is supplemented in diets containing corn DDGS, and this has been largely attributed to the level of NDF within the diet, and the composition of corn arabinoxylan ( Jacela et al, 2010 ; Kerr et al, 2013 ).…”
Section: Discussionsupporting
confidence: 90%
“…This implies that CE can promote protein deposition in piglets when protein metabolises while maintaining decomposition levels across treatments. Urea is the main N-containing bi-product of amino acid catabolism and has a strong linear relationship to the PUN concentration [26]. Compared with CON, piglets fed with CE had increases in urea circulating AA in the plasma and also had the highest urea content.…”
Section: Discussionmentioning
confidence: 99%
“…The feed consumption was measured every day to calculate the average daily feed intake (ADFI) and feed to gain ratio (F/G). Fresh fecal grab samples were collected in the morning during the last week (experimental d [21][22][23][24][25][26][27][28] and pooled by pen and stored at −20 • C for N and P emissions analysis. Each piglet was weighed at the end of the experiment, the two pigs closest to the average weight of treatments were selected from each replicate pen for slaughter.…”
Section: Sample Collection and Slaughter Proceduresmentioning
confidence: 99%
“…and Lactobacillus spp.) in pigs [13][14][15][16] . However, sequence-based microbial profiling of enzyme-supplemented pigs has not been conducted to date and the microbial species that most efficiently utilise xylose, arabinose and glucans are as yet unknown.…”
mentioning
confidence: 99%